SURGICAL MANAGEMENT OF VENTRAL HERNIA IN A CAT: A CASE REPORT - Lefira; I Gusti Agung Gde Putra Pemayun; Anak Agung Gde Jayawardhita (Buletin Veteriner Udayana, 2025)
Ventral hernia, characterized by incomplete peritoneal closure in the abdominal midline, results in formation of a hernial ring permitting organ protrusion. This case report describes a 2-year-old, 3 kg female mixed-breed cat presenting with a reducible ventral abdominal mass persisting for two months. Physical examination revealed a palpable, reducible bulge with positive tissue elasticity. Radiographic confirmation identified omental and intestinal contents within the hernial sac. The patient underwent herniorrhaphy under general anesthesia induced by xylazine-ketamine combination (1 mg/kg and 5 mg/kg IV, respectively). Surgical management involved content reduction and anatomical layer closure. Postoperative care included intravenous cefotaxime (20 mg/kg q12h for 72 hours) transitioning to oral cefixime (10 mg/kg q12h for 96 hours). By postoperative day 8, complete recovery was evidenced by wound epithelialization, normal appetite, and unimpaired elimination. This case underscores the importance of prompt surgical intervention for ventral hernias to prevent incarceration complications.